Utilización de las tics en la resolución de problemas de matemática en los estudiantes de la carrera de ciencias exactas. - Moreta Chango, Alex Marcelo (2017)
This research seeks to know the use of TICS in solving math problems in students of the exact sciences of the Faculty of Education Sciences, Humanities and Technologies of the UNACH, since today we are In the technological age and therefore the education can not be left behind so it has to go hand in hand with the use of TICS to be able to obtain better results in the teaching-learning of our students who will be future teachers, for that it was developed A test according to the contents of the syllabus of each semester so that the students of our race solve it with the use of any software that they think convenient. This instrument was applied to 44 students for the collection of data the same ones that were processed statistically using the Microsoft Excel 2013 tool, with descriptive statistics techniques. At the end of the resolution of the test was determined that the software most used by students in solving mathematical problems is Geogebra but at the same time almost the same number of students does not use any software to solve math problems in solve it Traditional way. Finally, it is recommended to strengthen the use of TICS, with the application of different methodologies, methods and techniques in the curriculum grid of each semester to obtain better results.